Kinerja Subsidi Pupuk di Indonesia - Aida Ratna Zulaiha; Rita Nurmalina; Bunasor Sanim (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
The implementation of fertilizer subsidies in Indonesia involves large government budgets, varied stakeholders, and complex business processes. Therefore, the performance of the government on the investment in fertilizer subsidies, worth almost Rp40 trillion or more than 30% of the total non-energy subsidies, needs to be analyzed. The objective of this research was to analyze the performance of fertilizer subsidies through factors affecting fertilizer subsidy budget and ‘six appropriate achievements’ of the fertilizer subsidies in Indonesia. Panel data regression and descriptive analysis were conducted on the secondary data of 2011–2015 in 32 provinces. The results showed that fertilizer subsidy performance, as reflected by the availability of fertilizer subsidy budget, was significantly affected by the absorption of subsidized fertilizer in the previous year, government debt to fertilizer producers, assistance fund to provincial government, and GDRP. With a value over 90 percent, the performances of fertilizer subsidies in ‘six appropriate types’, were achieved on ‘appropriate type’ and ‘appropriate quantity’. The ‘appropriate location’ of each province was in the range of 30-96%.Keywords: fertilizer subsidy, panel data regression, descriptive analysis, subsidy budget, six appropriateAbstrak: Pelaksanaan subsidi pupuk di Indonesia melibatkan anggaran pemerintah yang besar, pemangku kepentingan yang beragam dan bisnis proses yang kompleks. Oleh karena itu, investasi pemerintah dalam subsidi pupuk yang nilainya hampir Rp40 triliun atau lebih 30% dari total subsidi non energi tersebut perlu dianalisis kinerjanya. Tujuan dari penelitian ini adalah menganalisis kinerja subsidi pupuk melalui faktor-faktor yang memengaruhi anggaran subsidi pupuk dan pencapaian ‘enam tepat’ subsidi pupuk di Indonesia. Regresi data panel dan analisis diskriptif dilakukan dengan menggunakan data sekunder tahun 2011–2015 dan 32 provinsi. Hasil analisis menunjukkan bahwa kinerja subsidi pupuk yang dicerminkan oleh ketersediaan anggaran subsidi pupuk signifikan dipengaruhi oleh penyerapan pupuk bersubsidi pada tahun sebelumnya, hutang subsidi pemerintah kepada produsen, dana pendampingan pemerintah pusat kepada pemerintah provinsi dan PDRB. Dengan nilai di atas 90%, kinerja subsidi pupuk dalam ‘enam tepat’ tercapai pada ‘tepat jenis’, dan ‘tepat jumlah’. Kinerja subsidi pupuk dalam ‘tepat tempat’ pada tiap provinsi tercapai pada kisaran 30–96%.Kata kunci: subsidi pupuk, regresi data panel, analisis diskriptif, anggaran subsidi, enam tepat